2010
DOI: 10.1111/j.1365-2648.2010.05532.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a course on the prevention and control of the smoking habit on its prevalence and incidence among students of health sciences

Abstract: The intervention suggests the effect on habit acquisition was slight but not so on cessation. Preventive interventions should be carried out before students go to university, while more specific cessation programmes are required to reduce tobacco use among students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
1
2
Order By: Relevance
“…The mean value is superior than the results from two studies carried out amongst Medicine students (26.1%) and Physiotherapy and Nursing students (27.3%), in 2009 and 2011, respectively [35,36]. However, worldwide studies have reported a prevalence of smoking amongst university students with a similar range of consumption as we present in this study.…”
Section: Resultscontrasting
confidence: 87%
“…The mean value is superior than the results from two studies carried out amongst Medicine students (26.1%) and Physiotherapy and Nursing students (27.3%), in 2009 and 2011, respectively [35,36]. However, worldwide studies have reported a prevalence of smoking amongst university students with a similar range of consumption as we present in this study.…”
Section: Resultscontrasting
confidence: 87%
“…Alcohol is the most consumed substance (78.3%), a value that are high but similar to those found by different authors in Spanish university students in recent years (López López, Santín Vilariño, Torrico Linares, & Rodríguez González, 2003;Mota, Alvarez-Gil, Corral, Rodríguez Holguín, Parada, Crego, Caamaño-Isorna, & Cadaveira, 2010;Vázquez, Blanco, & Torres Iglesias, 2006) and somewhat higher that those detected by the National Health Survey in 2006 (Instituto Likewise, the tobacco habit showed values close to those found by the National Health Survey for this age range and other authors' observations in university populations (Jiménez-Muro Franco et al, 2009;Martín, Molina, Fernández, Fernández, de Abajo, & Delgado, 2011) Our results regarding illegal drug use were somewhat lower than those found by Jiménez-Muro Franco et al (2009), who found percentages of over 50% in men and women, and by Font-Mayolas, Gras, & Planes, (2006), with rates of 75% for men and 50% for women, but were nevertheless worrying.…”
Section: Substance Use Prevalencessupporting
confidence: 47%
“…However, as nurses take on greater roles in smoking cessation efforts (Martín et al . ), the low rates of prescribing nicotine substitutes reinforce the need for ongoing pharmacology training and multidisciplinary teamwork in patient education and the management of chronic conditions.…”
Section: Discussioncontrasting
confidence: 70%
“…nitrates and oral antibiotics not available over the counter) and therefore are more relevant to physician responsibilities. However, as nurses take on greater roles in smoking cessation efforts (Mart ın et al 2011), the low rates of prescribing nicotine substitutes reinforce the need for ongoing pharmacology training and multidisciplinary teamwork in patient education and the management of chronic conditions. Approximately half of our respondents did not consider physicians to be the only beneficiary of nurse prescribing.…”
Section: Discussionmentioning
confidence: 99%